Renal Artery Stenosis, Diagnosis and Management: a Literature Review - I. A. Idrisov; T. N. Khafizov; R. R. Khafizov; I. Kh. Shaymuratov; E. E. Abhalikova; L. R. Idrisova (Креативная хирургия и онкология, 2021)
Peripheral arterial atherosclerosis, i.a., in renal arteries, is quite a regular pathology. Despite long clear aetiology and pathogenesis, a unified systemic management approach in such patients is still lacking. We have reviewed and analysed classical academic resources and scientific record databases (Cochrane Library, PubMed and Google Scholar) in the topic and engaged self-experience on the observation and treatment of patients with stenotic peripheral arteries. Ultrasonic duplex scanning (USDS) of renal arteries is the most accessible and cost-effective screening method to date. Among non-invasive techniques are magnetic resonance imaging (MRI) and contrast-enhanced multislice computed tomography (MSCT). Subtraction angiography remains the gold standard for deciding a surgical treatment, and intravascular diagnostic capacities grow as well. Today’s interventional radiology is powered by fractional flow reserve (FFR) measurement, intravascular ultrasound (IVUS) and optical coherence tomography (OCT).The management of patients with narrowed renal arteries remains relevant and requires further insight. A continuing accumulation and synthesis of experience in diagnosis and treatment of peripheral arterial stenosis is imperative. Current medicine relies on high technologies in the discovery and treatment of peripheral arterial stenosis. The quality of patient management directly relates to the hospital technical and financial level, the personnel competence and mastery of current state-of-the-art.